Pengaruh Pengetahuan Produk Terhadap Keputusan Menjadi Donatur Baitul Maal Hidayatullah Cabang Kediri - Dita Permata Syafitri; Atina Shofawati (Universitas Airlangga, 2014)
This research aims to discover the influences of product knowledge including product knowledge product knowledge as bundle of attributes, product knowledge as bundle of benefits, and product knowledge as value satisfiers towards the decision of being donors in Baitul Mall Hidayatullah Branch Kediri, especially in the middle of development of Intitution of Alms Amil (Amil Zakat) in Indonesia.This research uses quantitave descriptive approach. The sampling technique used in this research is probability sampling, i.e. a sampling technique which provides equal opportunity to each member of the population to be selected as sample members. The sampling is conducted by using simple random sampling. The number of samples in this research is 75 people. The technique analysis which is used is analysis of multiple linear regressions.The results of the research show that there is similarity of regression Y = 0,409 + 0,473 X1 + 0,194 X2 + 0,214 X3. Product knowledge has simultaneously influenced the decision of being donors in Baitul Mall Hidayatullah Branch Kediri with R Square 0, 594. Product knowledge including product knowledge as bundle of attributes, product knowledge as bundle of benefits, and product knowledge as value satisfiers has partially influenced the decision of being donors. The variable of product knowledge as bundle of attributes appears to be dominant in influencing the decision of being donors.Baitul Mall Hidayatullah Branch Kediri is suggested to improve the content of its bulletin. The bulletin distributed to prospective donors or donors should contain more complete, informative, and educative information since it plays quite important roles. The government is also expected to support the program of alms (zakat) centralization to be used as social importance and to reduce the poverty in Indonesia, instead of being in debt. REFERENCESAnshori, Muslich dan Sri Iswati. 2009. Buku Ajar Metodologi Penelitian Kuantitatif. Cetakan Pertama. Surabaya: Airlangga University Press.Engel, F. James; Roger D. Blackwell; Paul W. Miniard. 1995. Perilaku Konsumen. Jakarta : Binarupa Aksara.Kartajaya, Hermawan dan Muhammad Syakir Sula. 2006. Syariah Marketing. Bandung: PT. Mizan Pustaka.Kotler, Philip dan Gary Amstrong. 2008. Prinsip-Prinsip Pemasaran. Edisi 12, Jilid 1. Terjemahan. Jakarta: Erlangga________, dan Kevin Lane Keller. 2009. Manajemen Pemasaran. Edisi 13, Jilid 1. Jakarta: Erlangga.Kuncoro, Mudrajad. 2011. Metode Kuantitatif: Edisi Keempat. Yogyakarta: UPP STIM YKPNMuflih, Muhammad. 2006. Perilaku Konsumen Dalam Perspektif Ilmu Ekonomi Islam. Jakarta : Rajawali Pers.Peter, J. Paul dan Jerry C. Olson. 1999. Perilaku Konsumen dan Strategi Pemasaran. Edisi Keempat, Jilid 1. Jakarta: Erlangga.Santoso, Slamet. 2010. Metode Penelitian Kuantitatif: Plus Aplikasi Program SPSS. Ponorogo: P2-FE Universitas Muhammadiyah Ponorogo.Silalahi, Gabriel Amin.2003. Metodologi Penelitian dan Studi Kasus. Sidoarjo: Citra Media.Sugiyono. 2010a. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta.________. 2010b. Statistika untuk Penelitian. Bandung: Alfabeta.Sula, Syakir. 2011. Marketing Syariah (Online), (http://www.syakirsula.com/view/ article/ marketing-syariah/, Diakses Tanggal 17Juli 2013).Ratnasari, Ririn Tri dan Mastuti H. Aksa. 2009. Slide Perkuliahan Pemasaran Syariah. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Wirjana, Bernardine E. 2007. Mencapai Manajemen Berkualitas: Organisasi, Kinerja Program. Yogyakarta: Andi Offset